Effect of fractal dimension on sand-geosynthetic interface shear strength - Ari, Abdulmuttalip; Akbulut, Suat (ELSEVIER, 2022)
In this research, the effects of particle shape and surface structure on sand-geosynthetic interface shear strength were quantitatively investigated using fractal theory. Three different sand samples were prepared by considering the particle shape with overall regularity. Three geomembranes with different surface roughness and three EPS geofoams with various densities were selected to include the effect of surface roughness and hardness on the interface shear strength. Sand particles and geosynthetic surfaces were analyzed using image processing technique to measure the fractal dimension of the materials. Modified direct shear tests were performed to reveal the relationship between fractal dimension and interface shear strength. The shear tests pointed out that interface shear strength between sand and geosynthetic depends on both fractal dimension of materials (sand particles and geosynthetics) and surface hardness of geosynthetics. The proposed interface shear strength requires a complete approach rather than focusing on discrete effects. (c) 2022 Elsevier B.V. All rights reserved.
Keywords: Fractal dimension; Interface shear strength; Geomembranes; EPS geofoams; Sand; SIZE DISTRIBUTION; PARTICLE-SHAPE; SOIL; BEHAVIOR; ROUGHNESS; ROUNDNESS; FRICTION; MORPHOLOGY; MECHANISM; DENSITY; Engineering